Online Learning In Algerian Universities And Institutions: The Reality And Expectations - رحماني , أسماء (مجلة المقدمة للدراسات الانسانية و الاجتماعية, 2023)
The present descriptive research attempts to investigate the extent to which Algerian university teachers and learners accept online learning. Also, it tries to depict teachers’ and learners’ readiness towards such adoption. To collect the needed data, two emailed questionnaires were sent to a representative sample of 17 teachers and 79 learners selected from the whole population that comprises university teachers and learners at the department of Media and Communication, faculty of Humanities and Social Sciences, university of Batna-1. The selection was based on the simple random sampling technique. The obtained results were coded, and treated using the statistical package for social sciences (SPSS). The main findings of this research prove that teachers’ as well as learners’ reactions differ toward the adoption of this type of learning. Ultimately, their comments and suggestions pave the way to the success of online learning in the Algerian universities if the needed modifications are implemented.